Stories of hope, imagination, and transformative learning: A dialogue. Issue 177 (14th February 2023) - Butterwick, Shauna; Lawrence, Randee Lipson
Abstract: This article focuses on imagination and the role it can play in bringing about transformation. Through telling stories of feminist activism and teaching, we consider how imagination can extend our understanding of transformative learning. We examine how creative expression and various art forms have enabled imagination and consider the conditions needed to support such processes. We bring attention to the central role of imagination and hope in movements for social justice.